A Spatial Livability Index for dense urban centers. (September 2021) - Benita, Francisco; Kalashnikov, Vyacheslav; Tunçer, Bige
This article introduces a Spatial Livability Index based on geographically weighted principal component analysis. We study the case of 203 subzones in Singapore which are dense geographic boundaries in terms of population and built-up area. These regions share spatial correlations of objective measures of livability such as open spaces or community facilities. The proposed objective indicator captures the "hidden" patterns of livability provided by neighboring locations. Moreover, the results allow to identify atypical areas, that is geographical units that score very good/bad under the spatial approach but very bad/good under the non-spatial framework of livability.